PERANCANGAN SISTEM e-MCU DI PT CITO PUTRA UTAMA BERBASIS SMS GATEWAY (Information Technology and Telematics, 2014)
Abstract - The system offers an important part in the operation of the company, during the bidding process conducted by the medical examination only to the method of bidding or offering door to door manually, to let them know the latest price package MCU to those customers requiring a very long time and less effective and efficient for medical check-up paketan price (MCU) is very volatile. The end result of this research is e-MCU system at PT. First Son Cito based SMS Gateway can be used to send and reply to incoming smsautomatically according to the given format.Keywords – e-MCU, SMS Gateway, Delphi,MySQL